Situating Some Aspects of the Scholarship of Teaching and Learning (SoTL) in South African Higher Education Within Southern Theories - Chaka, Chaka; Shange, Thembeka; Ndlangamandla, Sibusiso Clifford; Mkhize, Dumisile (Journal of Contemporary Issues in Education, 2022)
This paper discusses aspects of the scholarship of teaching and learning (SoTL) in South African higher education (HE) and locates it within what it calls Southern theories. Three examples of such theories that the paper advances are Southern decolonial theory, decoloniality, and transversality, which it frames from the Global South standpoint. Concerning the first theory, the paper argues that SoTL, both as a notion and as a practice, needs to be problematized, critiqued, and contextualized according to the Global South HE settings in which it is applied. One of its key points in this regard is that SoTL has to question and critique the dominant epistemic practices and scholarly practices underpinning the curricula of Global South higher education institutions (HEIs), and through which students are framed in these HEIs. With reference to both decoloniality and transversality, the paper foregrounds components of SoTL that are aligned to these two approaches in a way that dismantles their hierarchical relations. Most importantly, it contends that transversality is capable of decentering Western truth claims in favor of polycentric epistemologies, frameworks, and methodologies that resonate with and that have applicability to the Global South.